Conversion of Bacillus subtilis 168 to a subtilin producer by competence transformation. - Liu, W (1991)
Subtilin is a ribosomally synthesized peptide antibiotic produced by Bacillus subtilis ATCC 6633. B. subtilis 168 was converted to a subtilin producer by competence transformation with chromosomal DNA from B. subtilis ATCC 6633. A chloramphenicol acetyltransferase gene was inserted next to the subtilin structural gene as a selectable marker. The genes that conferred subtilin production were derived from a 40-kb region of the B. subtilis ATCC 6633 chromosome that had flanking homologies to the B. subtilis 168 chromosome. The subtilin produced by the mutant was identical to natural subtilin in its biological activity, chromatographic behavior, amino acid composition, and N-terminal amino acid sequence.